2021
DOI: 10.1111/jfbc.13912
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Volvariella volvacea inhibit fat accumulation in C. elegans dependent on the aak‐2/nhr‐49‐mediated pathway

Abstract: Volvariella volvacea has bioactivities in improving immunity, anti‐oxidation, and alleviating obesity, which is an excellent functional food. Polysaccharide from Volvariella volvacea (VPS), one of the main bioactive components, exerts a potential fat‐lowering effect, but its exact mechanism remains unclear. In this study, the effects and molecular pathways of VPS regulate the fat deposition of Caenorhabditis elegans. Results showed that VPS at low (250 μg/ml), medium (500 μg/ml) and high (750 μg/ml) concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Known polysaccharides with bile acid binding activity were also isolated from Abelmoschus esculentus [ 62 ], Kadsura coccinea [ 63 ], and Laminaria japonica [ 64 ], and in all cases, the presence of uronic acids was determined as a basic principle for effect manifestation [ 65 ]. The lipid lowering effect of Inonotus obliquus and Volvariella volvacea polysaccharides was associated with their fat and cholesterol binding [ 66 , 67 ], providing the hypolipidemic activity of polymers. In addition, the pancreatic lipase inhibition plays an important role in the lipid lowering effect of plant food and polysaccharide-derived products.…”
Section: Resultsmentioning
confidence: 99%
“…Known polysaccharides with bile acid binding activity were also isolated from Abelmoschus esculentus [ 62 ], Kadsura coccinea [ 63 ], and Laminaria japonica [ 64 ], and in all cases, the presence of uronic acids was determined as a basic principle for effect manifestation [ 65 ]. The lipid lowering effect of Inonotus obliquus and Volvariella volvacea polysaccharides was associated with their fat and cholesterol binding [ 66 , 67 ], providing the hypolipidemic activity of polymers. In addition, the pancreatic lipase inhibition plays an important role in the lipid lowering effect of plant food and polysaccharide-derived products.…”
Section: Resultsmentioning
confidence: 99%
“…The enzymatic determination of the TG levels can be used to study changes in the total TG content due to genetic perturbations, dietary changes, or pharmacological disturbances. Recently, using the enzymatic measurements of TAGs, the fat-reducing effects of some natural product, active ingredients, such as polysaccharides from Auricularia auricula [ 222 ], Volvariella volvacea [ 223 ], bitter melon [ 224 ] as well as phenolics from strawberry and raspberry [ 225 ], have been identified in C. elegans . In another study, Crawford and co-workers applied the enzymatic measurements of TGs and found that the lipid content of the diet could modify the lipid accumulation caused by methylmercury [ 226 ].…”
Section: Experimental Tools For the Studies Of Fat Metabolism In ...mentioning
confidence: 99%
“… Bioactive Compound Source Bioactivities Studied C. elegan s strain used Evaluation used Reference Carbohydrates Barley β-glucan Anti-obesity N2 Lifespan; Oil red staining; Triglyceride assay; RT-PCR; SCFA assay; Xiao et al (2020) Betaxanthins Antioxidant N2; TJ375 Lifespan; Quantification of hsp-16 . 2::GFP Guerrero-Rubio et al (2021) Bitter Melon (Momordica charantia) Anti-obesity N2; mu86; e1370; nr2014; tm420; tm331; wa36 Lifespan; Oil red staining; Triglyceride level; RT-PCR Zhu et al (2021) Casein-maltodextrin Maillard Conjugates Antioxidant; anti-aging N2 Lifespan; Thermal stress; Lipofuscin level; SOD and CAT activity Sun et al (2021) Fructan exopolysaccharides Antioxidant N2; TJ356 Survival under oxidative stress; Lifespan; Daf-16 localization; Lakra et al (2021) Fucoidan from algae ( Fucus vesiculosus, Undaria pinnatifida, Macrocystis pyrifera) Antimicrobial N2 Bacterial Quantification Palacios-Gorba et al (2020) Resistant starch; Fermented starch; Short chain fatty acids Anti-obesity N2 Red Niles staining Zheng et al (2010) Straw mushroom ( Volvariella volvacea ) Anti-obesity N2; ok524; mu86; nr2041; tm420; tm331; wa36; tm3116 Locomotive behavior; worm size; growth rate; reproductive assay; Oil red staining; Triglyceride quantification; RT-PCR; Detection of GFP-labeled proteins Bai et al (2021) Wheel wingnut ( Cyclocarya paliurus ) Anti-obesity N2; XA7702; RB1716; CE541; CE548; BX107; BX106; BX153; BX160; BX110; WBM170; ZXW618 Triglyceride quantification; Oil red staining; Lipid droplet analysis; Pharyngeal pumping assays; Body size assay; RT-PCR; Visualization of SBP-1::GFP and ACS-2::GFP Lin et al (2020) …”
Section: Application Of C Elegans To Study Bioacti...mentioning
confidence: 99%
“…Further assessment of the fermented barley β-glucan determined that its upregulation of nuclear hormone receptor 49 (nhr-49), enoyl-CoA hydratase (ech-1), carnitine palmitoyl transferase-1 (cpt-1), and carnitine palmitoyl transferase-2 (cpt-2) in nematodes likely contributed to the observed anti-obesity effect ( Xiao et al, 2020 ). Similarly, polysaccharides from a tropical species of edible mushroom Volvariella volvacea, reduced triglyceride levels by 24% in C. elegans and decreased the accumulation of fat through the aak-2/nhr-49-mediated fatty acid synthesis pathway ( Bai et al, 2021 ). It is known that C. elegans contain a mediator-15 gene (mdt-15), which is involved in the fatty acid metabolism pathway, and it has a homolog in humans, arc105 (Yang et al, 2006).…”
Section: Application Of C Elegans To Study Bioacti...mentioning
confidence: 99%